The art of tinkering : meet 150+ makers working at the intersection of art, science & technology - Wilkinson, Karen; Petrich, Mike; Exploratorium (Organization) (2013)
"The Art of Tinkering is a collection of exhibits, artwork, and projects that celebrate a whole new way to learn, in which people create their own knowledge through making and doing, working with readily available materials, getting their hands dirty, collaborating with others, problem-solving in the most fun sense of the word, and, yes, oftentimes failing and bouncing back from getting stuck. Each artist featured in The Art of Tinkering goes through this process, and lovingly shares the backstory behind their own work so that readers can feel invited to join in on the whimsy. Whether it's sharing their favorite tools (who knew toenail clippers could be so handy?) or offering a glimpse of their workspaces (you'd be amazed how many electronics tools you can pack into one pantry!), the stories, lessons, and tips in The Art of Tinkering offer a fascinating portrait of today's maker scene. Artists include Scott Weaver, Arthur Ganson, Moxie, Tim Hunkin, AnnMarie Thomas, Ranjit Bhatnagar and Jie Qi" -- Publisher's description.
Tinkering tenets -- Tools for tinkering -- The Tinkering Studio team -- Tinkering in the world -- A history of the sky -- The view from on high -- Physiological photograms -- Stroboscopic adventures -- Luminous installations -- Squishy circuits -- Electronic popables -- Wondrous wearables -- Felted tech -- Five words or less -- Wire works -- Pet or meat -- Animatronic creatures -- Cardboard girl -- Absurdist automata -- Conservation of intimacy -- Ocean edge device -- An instrument a day -- Technological lifeforms -- Fused fashions -- Cardboard supertrack -- Rolling through the bay -- Tapigami.
"Exploratorium"--Front cover.
"The Tinkering Studio"--Added title page.
Includes index.
Keywords: Science and the arts; Creative ability in technology; Technology; Inventions